Corneal Absorption of a New Riboflavin-Nanostructured System for Transepithelial Collagen Cross-Linking - Bottos, Katia M.; Oliveira, Anselmo Gomes de [UNESP]; Bersanetti, Patrícia A.; Nogueira, Regina F.; Lima-Filho, Acácio A. S.; Cardillo, José A.; Schor, Paulo; Chamon, Wallace (Public Library of Science (PLoS), 2013)
Corneal collagen cross-linking (CXL) has been described as a promising therapy for keratoconus. According to standard CXL protocol, epithelium should be debrided before treatment to allow penetration of riboflavin into the corneal stroma. However, removal of the epithelium can increase procedure risks. In this study we aim to evaluate stromal penetration of a biocompatible riboflavin-based nanoemulsion system (riboflavin-5-phosphate and riboflavin-base) in rabbit corneas with intact epithelium. Two riboflavin nanoemulsions were developed. Transmittance and absorption coefficient were measured on corneas with intact epithelia after 30, 60, 120, 180, and 240 minutes following exposure to either the nanoemulsions or standard 0.1% or 1% riboflavin-dextran solutions. For the nanoemulsions, the epithelium was removed after measurements to assure that the riboflavin had passed through the hydrophobic epithelium and retained within the stroma. Results were compared to de-epithelialized corneas exposed to 0.1% riboflavin solution and to the same riboflavin nanoemulsions for 30 minutes (standard protocol). Mean transmittance and absorption measured in epithelialized corneas receiving the standard 0.1% riboflavin solution did not reach the levels found on the debrided corneas using the standard technique. Neither increasing the time of exposure nor the concentration of the riboflavin solution from 0.1% to 1% improved riboflavin penetration through the epithelium. When using riboflavin-5-phosphate nanoemulsion for 240 minutes, we found no difference between the mean absorption coefficients to the standard cross-linking protocol (p = 0.54). Riboflavin nanoemulsion was able to penetrate the corneal epithelium, achieving, after 240 minutes, greater stromal concentration when compared to debrided corneas with the standard protocol (p = 0.002). The riboflavin-5-phosphate nanoemulsion diffused better into the stroma than the riboflavin-base nanoemulsion. © 2013 Bottos et al.
Keywords: adhesive agent; flavine mononucleotide; phosphatidylcholine; polysorbate 20; animal tissue; central corneal thickness; controlled study; cornea epithelium; cornea stroma; drug absorption; drug diffusion; drug penetration; drug stability; hydrophobicity; long term exposure; nanoemulsion; nanopharmaceutics; nonhuman; physical chemistry; protein cross linking; rabbit; zeta potential